2021
DOI: 10.1016/j.ijcard.2021.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of exercise limitation in contemporary paediatric Fontan patients with an extra cardiac conduit

Abstract: Background: Although various determinants of exercise limitation in Fontan patients have been studied, most research has been performed in patients who underwent different surgical procedures with differing haemodynamic characteristics. The aim of the current study was to evaluate non-invasively measured cardiovascular parameters and their influence on exercise performance in paediatric Fontan patients with an extracardiac conduit and moderate-good systolic ventricular function. Methods: Fontan patients, betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…Vascular dysfunction (increased arterial stiffness and endothelial dysfunction) is associated with worse aerobic exercise capacity (76)(77)(78). This is likely related to impaired skeletal oxygenation and muscle blood flow rather than the contribution of endothelial dysfunction to increased systemic vascular resistance (elevated afterload) in the setting of limited preload reserve (41,79).…”
Section: Systemic Vascular Resistance and Vascular Functionmentioning
confidence: 99%
“…Vascular dysfunction (increased arterial stiffness and endothelial dysfunction) is associated with worse aerobic exercise capacity (76)(77)(78). This is likely related to impaired skeletal oxygenation and muscle blood flow rather than the contribution of endothelial dysfunction to increased systemic vascular resistance (elevated afterload) in the setting of limited preload reserve (41,79).…”
Section: Systemic Vascular Resistance and Vascular Functionmentioning
confidence: 99%
“…This is in line with the findings by Claessen et al and Hedlund et al, who also demonstrated regular HR response and speculated that reduced HR peak in Fontan patients might be an expression of a physiological reaction to maintain SV and Qc within the context of Frank–Starling mechanism, because of reduced preload ( 35 , 36 ). In addition, due to the numerous operations, many Fontan patients have a lack of responsiveness to modulation by the autonomic nervous system and an impaired sinus node function, both with the consequence of a limited HR variability and HR reserve ( 13 , 37 , 38 ). Here, similar to previous studies, Fontan patients showed significantly lower HR peak compared to controls, but these values were measured at significant lower P peak ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies reported significantly lower VO 2peak , 17,18,[21][22][23][24] VO 2 at anaerobic threshold, 17,23,25 and O 2 pulse 17,21 relative to healthy individuals. Although reductions in both maximal and submaximal exercise capacity have been reported, 26 submaximal exercise parameters are typically less reduced than those for maximal exercise. 27 Cardiac response.…”
Section: Cardiovascular Response and Exercise Capacitymentioning
confidence: 96%
“…Reported values for the mean peak heart rate ranged from 142.2 AE 24.8 bpm 17 to 173.5 AE 16.0 bpm 26 (Table 1). Multiple studies reported that, compared with healthy controls, paediatric Fontan patients demonstrated significantly diminished peak stroke volume, 26 peak heart rate, 17,18,21,24,28 maximal heart rate, 23,29,30 heart rate gradient, 17 maximal heart rate response, 28,31 maximal stroke index, 23 stroke index response, 23 O 2 pulse, 30 and exercising O 2 saturation. 17 Two studies reported significantly decreased submaximal heart rate response, 28,31 and it was suggested by Banks et al 28 that paediatric Fontan patients may experience enhanced submaximal exercise efficiency relative to healthy individuals.…”
Section: Cardiovascular Response and Exercise Capacitymentioning
confidence: 99%